Secular stagnation and COVID-19 - Stradomski, Maciej; Schmidt, Katarzyna (Stagnacja sekularna a Covid-19, 2020)
The main aim of the article is to start a discussion about the pandemic COVID-19 in the context of secular stagnation. The secular stagnation phenomenon was reintroduced by L. Summers in 2013, who claimed that after the global financial crisis of 2007-2009, advanced economies were trapped in an era of low and sluggish growth and a low-interest rates environment. Now, with the occurrence of coronavirus many things have changed, therefore the authors tried to analyse the structural determinants of secular stagnation and the potential impact of the crisis on these factors. The authors concluded that the coronavirus crisis might be a breaking point that will change the global economy but the character and novelty of the crisis make it difficult to predict future outcomes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 199-212